Surface modification of coconut shell based activated carbon for the improvement of hydrophobic VOC removal - Li, Lin; Liu, Suqin; Liu, Junxin (Journal of hazardous materials, 2011)
► Coconut shell based carbons were chemically treated by alkalis and acids. ► GAC modified by alkalis had better o-xylene adsorption capacity. ► We analyzed textural and surface chemistry changes induced on the GAC. ► Reducing hydrophilic carbon surface favors abatement of hydrophobic VOCs. ► Reducing hydrophilic carbon surface results in less adsorbent regeneration. In this study, coconut shell based carbons were chemically treated by ammonia, sodium hydroxide, nitric acid, sulphuric acid, and phosphoric acid to determine suitable modification for improving adsorption ability of hydrophobic volatile organic compounds (VOCs) on granular activated carbons (GAC). The saturated adsorption capacities of o-xylene, a hydrophobic volatile organic compound, were measured and adsorption effects of the original and modified activated carbons were compared. Results showed that GAC modified by alkalis had better o-xylene adsorption capacity. Uptake amount was enhanced by 26.5% and reduced by 21.6% after modification by NH 3H 2O and H 2SO 4, respectively. Compared with the original, GAC modified by acid had less adsorption capacity. Both SEM/EDAX and BET were used to identify the structural characteristics of the tested GAC, while IR spectroscopy and Boehm's titration were applied to analysis the surface functional groups. Relationships between physicochemical characteristics of GAC and their adsorption performances demonstrated that o-xylene adsorption capacity was related to surface area, pore volume, and functional groups of the GAC surface. Removing surface oxygen groups, which constitute the source of surface acidity, and reducing hydrophilic carbon surface favors adsorption capacity of hydrophobic VOCs on carbons. The performances of modified GACs were also investigated in the purification of gases containing complex components ( o-xylene and steam) in the stream.